2013
DOI: 10.1186/1471-2369-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Association between family members of dialysis patients and chronic kidney disease: a multicenter study in China

Abstract: BackgroundFamily members of patients with end stage renal disease were reported to have an increased prevalence of chronic kidney disease (CKD). However, studies differentiated genetic and non-genetic family members are limited. We sought to investigate the prevalence of CKD among fist-degree relatives and spouses of dialysis patients in China.MethodsSeventeen dialysis facilities from 4 cities of China including 1062 first-degree relatives and 450 spouses of dialysis patients were enrolled. Sex- and age- match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 38 publications
(34 reference statements)
6
29
2
Order By: Relevance
“…In comparison with our previous study that screened silent kidney disease in asymptomatic individuals in Hong Kong, the present study reported a significantly higher prevalence of proteinuria (23.1% vs. 3.0%, P < 0.0001), haematuria (25.9% vs. 17.0%, P < 0.0001) and glycosuria (4.4% vs. 1.9%, P = 0.001), respectively . Furthermore, the prevalence of proteinuria (23.1%) in relatives of CKD patients in this study was higher than that from two regional studies in China (Wei et al : 12.9%; Kong et al : 14.4%), and from two population‐based screening programmes in the United States (9.9%) and United Kingdom (9.5%) . However, the proportion of first‐degree relatives with eGFR ≤60 mL/min per 1.73 m 2 was lower (0.5%) than that from two regional studies in China (Wei et al : 7.9%; Kong et al : 1.5%).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In comparison with our previous study that screened silent kidney disease in asymptomatic individuals in Hong Kong, the present study reported a significantly higher prevalence of proteinuria (23.1% vs. 3.0%, P < 0.0001), haematuria (25.9% vs. 17.0%, P < 0.0001) and glycosuria (4.4% vs. 1.9%, P = 0.001), respectively . Furthermore, the prevalence of proteinuria (23.1%) in relatives of CKD patients in this study was higher than that from two regional studies in China (Wei et al : 12.9%; Kong et al : 14.4%), and from two population‐based screening programmes in the United States (9.9%) and United Kingdom (9.5%) . However, the proportion of first‐degree relatives with eGFR ≤60 mL/min per 1.73 m 2 was lower (0.5%) than that from two regional studies in China (Wei et al : 7.9%; Kong et al : 1.5%).…”
Section: Discussioncontrasting
confidence: 82%
“…The presence of a first‐degree or second‐degree relative with ESRD was reported to increase the risk of developing ESRD by 3‐ to 5‐fold in Americans . In addition, subsequent studies revealed that a significant proportion of relatives of CKD patients had clinically ‘silent’ kidney diseases, which was manifested as asymptomatic proteinuria and/or microscopic haematuria . The reported prevalence of CKD in relatives of CKD patients ranged from 14% to 30% .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The FRS allows for estimation of the individual’s 10-year risk of coronary heart disease by using traditional cardiac risk factors including age, gender, systolic BP, total cholesterol, HDL-C, and smoking status [7]. Previous studies found familial aggregation of traditional CVD risk factors, such as hypertension, diabetes, dyslipidemia, smoking and obesity among family members of CKD or ESRD patients [10], [30], [31], [36], [37]. Genetic traits and the clustering of shared environmental exposures and health behaviors may contribute to higher FRS and atherosclerotic CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Family members of ESRD patients were reported to be at higher risks for development of CKD or ESRD [10][16]. In particular, CVD is the leading cause of death in this population [17].…”
Section: Introductionmentioning
confidence: 97%